2016
DOI: 10.1016/j.actamat.2016.08.066
|View full text |Cite
|
Sign up to set email alerts
|

Effects of welding and post-weld heat treatments on nanoscale precipitation and mechanical properties of an ultra-high strength steel hardened by NiAl and Cu nanoparticles

Abstract: The effects of welding and post-weld heat treatment (PWHT) on nanoscale coprecipitation, grain structure, and mechanical properties of an ultra-high strength steel were studied through a combination of atom probe tomography (APT) and mechanical tests. Our results indicate that the welding process dissolves all pre-existing nanoparticles and causes grain coarsening in the fusion zone, resulting in a soft and ductile weld without any cracks in the aswelded condition. A 550 °C PWHT induces fine-scale re-precipita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
23
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 41 publications
(25 citation statements)
references
References 54 publications
1
23
0
1
Order By: Relevance
“…It should be pointed out that the matrix of most Cu and NiAl nanoparticle-strengthened steels is primarily martensite, but contains a small amount of austenite, the amount of which depends on the alloy composition and heat-treatment histories. While most of the previous studies were focused mainly on the understanding of precipitation behavior of Cu and NiAl nanoparticles in the martensite and ferrite phases [15][16][17][18][19][20][21][22], limited detailed information is available on the precipitation behavior and related mechanism in the austenite phase.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…It should be pointed out that the matrix of most Cu and NiAl nanoparticle-strengthened steels is primarily martensite, but contains a small amount of austenite, the amount of which depends on the alloy composition and heat-treatment histories. While most of the previous studies were focused mainly on the understanding of precipitation behavior of Cu and NiAl nanoparticles in the martensite and ferrite phases [15][16][17][18][19][20][21][22], limited detailed information is available on the precipitation behavior and related mechanism in the austenite phase.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, in a welding study of a newly developed Cu/NiAl co-precipitation strengthened steel [22], we observed an interesting microstructure containing both martensite and austenite phases together with complex nanoscale precipitation behavior in the heat-affected zone. Although the thermal history of the heat-affected zone is complicated in nature, while for an understanding of the welding microstructure, it is interesting and important to study the precipitation behavior and interfacial segregation in the heat-affected zone.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations